CHOOSING THE OPTIMAL MODIFIER TO INCREASE THE ABSORBENCY OF THE DETAILS CAST FROM GADFIELD STEEL (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In this article, a crushing cone suitable for world templates, high quality to machinery manufacturing enterprises, resistant to mowing, high strength and such a variety of details, as well as the production of heavy industrial products, set the task of specialists and scientists in this field as important as improving the existing technology and technology. In turn, the increasing level of equipment improvement at machine-building production enterprises also requires a lot of attention to the quality of metals. It is indicated that steel enterprises, as a rule, do not have special equipment for processing steel. In such conditions, the only and very effective way to improve the quality of steel in practice is the processing of liquid metal with special complex modifier alloys in the steel casting department. Modification of metals and alloys (its variety) is a deep process of their existence, actively influencing the state of metal solutions in the crystallization period, by introducing small additives of substances (modifiers) that lead to a change in the morphology of mirrors additives.